ANALISIS YURIDIS HUKUMAN MATI TERHADAP TENAGA KERJA INDONESIA (TKI) DI MALAYSIA DARI SUDUT PANDANG HUKUM HAK ASASI MANUSIA INTERNASIONAL - Made Arik Tamaja; I Made Pasek Diantha; I Made Budi Arsika (Kertha Negara : Journal Ilmu Hukum, 2013)
This paper aims to analyze the effects of capital punishment especially on Overseas Indonesian Workers (OIWs) and analyze Malaysia’s responsibility to the International Human Rights Law (IHRL). The analysis method used in this research is deductive and literature study, where data analysis is used to determine the impact of capital punishment through secondary data gathering from combined government and international organizations sources. In order to achieve the goal of this paper, several international human rights documents inter alia Universal Declaration of Human Rights and International Covenant on Civil and Political Rights and also regional document namely ASEAN Human Rights Declaration, have been used to analyze Malaysia’s legal responsibility and moral responsibility on the implementation of capital punishment against Overseas Indonesian Workers.